UZM-8 molecular sieve, preparation method thereof, catalyst containing UZM-8 molecular sieve and application
The preparation of high-quality UZM-8 molecular sieve through hydrothermal crystallization reaction of composite template agents solves the problems of high synthesis cost and low catalytic activity, and realizes efficient liquid phase alkylation reaction between ethylene and benzene, which improves the selection of ethylbenzene sex and conversion rate.
Patent Information
- Application Number
- CN202310788296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The synthesis cost of UZM-8 molecular sieve is high, the product has low crystallinity, and there is still room for improvement in catalytic activity and ethylbenzene selectivity, especially in the liquid phase alkylation reaction between ethylene and benzene.
The hydrothermal crystallization reaction is carried out using composite template agents (including tetramethylammonium hydroxide, tetraethylammonium hydroxide and dimethyldiethylammonium hydroxide), to optimize raw material ratio and reaction conditions, and to prepare high crystallinity, A high specific surface area UZM-8 molecular sieve was used to prepare a catalyst for the alkylation reaction of ethylene and benzene.
It significantly reduces the synthesis cost of UZM-8 molecular sieve, improves its catalytic activity and ethylene conversion rate, enhances the selectivity of the target product ethylbenzene, and has good application prospects.
Smart Images

Figure CN119219022A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a UZM-8 molecular sieve and a preparation method thereof, a catalyst containing the UZM-8 molecular sieve and applications thereof. Background Art
[0002] As an important chemical raw material, ethylbenzene is mainly used for dehydrogenation to produce styrene, and then to produce styrene series resins such as polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN) and styrene-butadiene rubber (SBR), etc. At present, the main production processes of ethylbenzene are: AlCl3 method, Alkar gas phase method, catalytic distillation process molecular sieve gas phase method and molecular sieve liquid phase method; the first two methods have been gradually eliminated due to the shortcomings of environmental pollution, equipment corrosion, and high energy consumption. The molecular sieve liquid phase method is a process developed to address the shortcomings of the gas phase method. At present, the catalysts that have been industrialized in the liquid phase synthesis of ethylbenzene include Y, Beta and MCM-22 molecular sieve catalysts.
[0003] UZM-8 molecular sieve has an MWW topological structure and has been found to be useful for the liquid phase alkylation of ethylene and benzene. However, the synthesis cost of UZM-8 molecular sieve in the related art is high, the product crystallinity is relatively low, and the catalytic activity and ethylbenzene selectivity for the liquid phase alkylation of ethylene and benzene still have room for improvement. Summary of the invention
[0004] The purpose of the present disclosure is to provide a UZM-8 molecular sieve and a preparation method thereof, a catalyst containing the UZM-8 molecular sieve and an application thereof, so as to reduce the synthesis cost and improve the catalytic activity of the UZM-8 molecular sieve product.
[0005] In order to achieve the above object, the present disclosure provides a first aspect of a method for preparing a UZM-8 molecular sieve, the method comprising:
[0006] Carrying out a hydrothermal crystallization reaction on a raw material mixture containing a silicon aluminum source, a first template, a second template and water and recovering a product;
[0007] Wherein, the first template agent is at least one selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, and the second template agent is dimethyldiethylammonium hydroxide.
[0008] Optionally, the molar ratio of the first template to the second template is (0.1-1):1, preferably (0.25-0.67):1.
[0009] Optionally, the first template agent is tetramethylammonium hydroxide and tetraethylammonium hydroxide, and the molar ratio of the tetramethylammonium hydroxide to the tetraethylammonium hydroxide is (0.2-2):1.
[0010] Optionally, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=10-100, H2O / SiO2=8-50, R / SiO2=0.05-1.5;
[0011] Preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15-40, H2O / SiO2=9-40, R / SiO2=0.1-0.9;
[0012] More preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15-30, H2O / SiO2=10-20, R / SiO2=0.3-0.5;
[0013] Wherein, R represents the total molar number of the first template and the second template.
[0014] Optionally, the raw material mixture further contains an alkali source, and the molar ratio of the raw material mixture includes: B / SiO2=0.05-0.5, wherein B represents the molar number of the alkali source.
[0015] Optionally, the alkali source is at least one selected from sodium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide and cesium hydroxide.
[0016] Optionally, the silicon-aluminum source is silicon-aluminum gel.
[0017] Optionally, the conditions of the hydrothermal crystallization reaction include: a temperature of 130 to 180° C. and a time of 5 to 21 days;
[0018] Preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 130 to 160° C. and a time of 7 to 17 days;
[0019] More preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 150 to 160° C. and a time of 10 to 17 days.
[0020] In a second aspect of the present disclosure, a UZM-8 molecular sieve prepared by the method described in the first aspect of the present disclosure is provided.
[0021] According to a third aspect of the present disclosure, a catalyst is provided, which comprises a carrier and the UZM-8 molecular sieve described in the second aspect of the present disclosure, wherein the content of the UZM-8 molecular sieve is 30 to 90 wt%, preferably 70 to 80 wt%, based on the dry weight of the catalyst.
[0022] In a fourth aspect of the present disclosure, there is provided an application of the catalyst described in the third aspect of the present disclosure in a liquid phase alkylation reaction of ethylene and benzene, wherein the application comprises: reacting ethylene and benzene in the presence of the catalyst at a reaction temperature of 180 to 260° C., a reaction pressure of 2.0 to 4.0 MPa, and a benzene weight space velocity of 1 to 5 h -1 , the alkylation reaction is carried out under the condition that the molar ratio of benzene to ethylene is (2-12):1.
[0023] Through the above technical solution, the advantages of the present disclosure are:
[0024] (1) Compared with the UZM-8 molecular sieve synthesized by the traditional hydrothermal method, the present invention adopts a composite template agent to synthesize a UZM-8 molecular sieve with high crystallinity, high specific surface area and pore volume, while significantly reducing the synthesis cost of the molecular sieve.
[0025] (2) Compared with catalysts prepared from UZM-8 molecular sieves synthesized by other methods, the UZM-8 molecular sieve catalyst disclosed in the present invention has better catalytic activity in the liquid phase alkylation reaction of ethylene and benzene, which is beneficial to improving the ethylene conversion rate and / or the selectivity of the target product ethylbenzene, and has a good application prospect.
[0026] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0028] Figure 1 It is the XRD spectrum of the UZM-8 molecular sieve prepared in Example 1.
[0029] Figure 2 This is a SEM photograph of the UZM-8 molecular sieve prepared in Example 1. DETAILED DESCRIPTION
[0030] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0031] In a first aspect of the present disclosure, a method for preparing a UZM-8 molecular sieve is provided, the method comprising:
[0032] Carrying out a hydrothermal crystallization reaction on a raw material mixture containing a silicon aluminum source, a first template, a second template and water and recovering a product;
[0033] Wherein, the first template agent is at least one selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, and the second template agent is dimethyldiethylammonium hydroxide.
[0034] The present invention uses the first template and the second template as a composite template, and can synthesize high-quality UZM-8 molecular sieve under hydrothermal crystallization conditions, wherein the first template is selected from cheap quaternary ammonium base templates, which significantly reduces the synthesis cost.
[0035] According to the present disclosure, the molar ratio of the first template to the second template may be (0.1-1): 1. In order to further reduce the synthesis cost and improve the quality of the molecular sieve product, the molar ratio of the first template to the second template is preferably (0.25-0.67):1.
[0036] The first template is tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide or tetrabutylammonium hydroxide, or a combination of two or three thereof. In a preferred embodiment of the present disclosure, the first template is tetramethylammonium hydroxide and tetraethylammonium hydroxide, and the molar ratio of the tetramethylammonium hydroxide and the tetraethylammonium hydroxide can be (0.2-2):1. Using the above-mentioned ratio of tetramethylammonium hydroxide and tetraethylammonium hydroxide as the first template and the second template is compounded, which is conducive to further reducing the synthesis cost and improving the quality of the molecular sieve product.
[0037] According to the present disclosure, the molar ratio of the raw material mixture may include: SiO2 / Al2O3=10~100, H2O / SiO2=8~50, R / SiO2=0.05~1.5; preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15~40, H2O / SiO2=9~40, R / SiO2=0.1~0.9; more preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15~30, H2O / SiO2=10~20, R / SiO2=0.3~0.5; wherein R represents the total molar number of the first template and the second template.
[0038] In a specific embodiment of the present disclosure, the raw material mixture may further contain an alkali source, and the molar ratio of the raw material mixture further includes: B / SiO2=0.05-0.5, preferably, B / SiO2=0.10-0.3, wherein B represents the molar number of the alkali source. When the raw material mixture contains an alkali source, crystallization can be further promoted and the crystallization reaction time can be shortened. The alkali source may be an inorganic base. Further, the alkali source may be at least one selected from sodium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide and cesium hydroxide, preferably sodium hydroxide.
[0039] According to the present disclosure, the silicon-aluminum source is a substance that can provide silicon and aluminum. In a preferred embodiment, the silicon-aluminum source is silicon-aluminum gel. The silicon-aluminum molar ratio of the silicon-aluminum gel can be adjusted in a wide range. For example, the SiO2 / Al2O3 (molar ratio) of the silicon-aluminum gel is not less than 10. The silicon-aluminum gel can be sodium-containing silicon-aluminum gel, or sodium-free silicon-aluminum gel, preferably sodium-free silicon-aluminum gel. The silicon-aluminum gel can be commercially available or synthesized, and the present disclosure has no special restrictions.
[0040] According to the present disclosure, the conditions of the hydrothermal crystallization reaction may include: a temperature of 130 to 180°C and a time of 5 to 21 days; preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 130 to 160°C and a time of 7 to 17 days; more preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 150 to 160°C and a time of 10 to 17 days.
[0041] According to the present disclosure, the method for recovering the product is well known to those skilled in the art, and the process may include cooling the reactor after the crystallization is completed, separating the crystallized product from the mother liquor through solid, washing the solid with deionized water until the pH value is close to 7, drying and roasting to obtain the UZM-8 molecular sieve raw powder. The drying conditions may be: temperature of 80-120°C, time of 8-24h; the roasting conditions may be: temperature of 540-600°C, time of 3-6h.
[0042] In a second aspect of the present disclosure, a UZM-8 molecular sieve prepared by the method described in the first aspect of the present disclosure is provided.
[0043] The UZM-8 molecular sieve disclosed in the present invention has a flaky structure, and has high crystallinity, high specific surface area and pore volume. Specifically, the crystallinity of the UZM-8 molecular sieve can be above 90%, especially above 92%, and the specific surface area can be between 360 and 500 m 2 / g, the pore volume can be between 0.55 and 0.70 cm 3 The SiO2 / Al2O3 (molar ratio) of the UZM-8 molecular sieve disclosed in the present invention may be 18-50.
[0044] In a third aspect of the present disclosure, a catalyst is provided, wherein the catalyst comprises a carrier and the UZM-8 molecular sieve described in the second aspect of the present disclosure.
[0045] According to the present disclosure, the UZM-8 molecular sieve content of the catalyst can vary over a wide range. Specifically, based on the dry weight of the catalyst, the UZM-8 molecular sieve content can be 30 to 90% by weight, preferably 70 to 80% by weight; the carrier content can be 10 to 70% by weight, preferably 20 to 30% by weight.
[0046] The carrier may be a common carrier used to prepare a catalyst in the art, for example, the carrier may be an inorganic oxide, and further, the inorganic oxide may be at least one selected from silicon oxide, aluminum oxide, magnesium oxide, zirconium oxide and titanium oxide. Preferably, the inorganic oxide is aluminum oxide, specifically SB powder, dry rubber powder, aluminum sol and pseudo-boehmite.
[0047] According to the present disclosure, the preparation method of the catalyst can be conventional in the art. For example, it can include the steps of mixing the UZM-8 molecular sieve with a carrier, forming, drying and calcining; it can also include the step of first exchanging the UZM-8 molecular sieve with ammonium to reduce the alkali metal content, so that the alkali metal content in the catalyst calculated as alkali metal oxide is less than 0.05% by weight.
[0048] The catalyst provided by the present disclosure is suitable for a variety of catalytic reactions, such as the alkylation reaction of benzene and propylene, or other reactions such as aromatization, cracking, isomerization, etc., and has high catalytic activity, among which it is particularly suitable for the liquid phase alkylation reaction of ethylene and benzene.
[0049] In a fourth aspect of the present disclosure, there is provided use of the catalyst described in the third aspect of the present disclosure in a liquid phase alkylation reaction of ethylene and benzene.
[0050] According to the present disclosure, the application may include: reacting ethylene with benzene in the presence of the catalyst at a reaction temperature of 180 to 260° C., a reaction pressure of 2.0 to 4.0 MPa, and a benzene weight space velocity of 1 to 5 h -1 , the alkylation reaction is carried out under the condition that the molar ratio of benzene to ethylene is (2-12):1.
[0051] In a preferred embodiment of the present disclosure, the conditions of the alkylation reaction include: a reaction temperature of 200 to 260° C., a reaction pressure of 3.0 to 3.5 MPa, and a benzene weight space velocity of 3 h -1 , the molar ratio of benzene to ethylene is 12:1.
[0052] By using the catalyst provided by the present disclosure, a higher ethylene conversion rate and / or target product ethylbenzene selectivity can be achieved in the process of synthesizing ethylbenzene by liquid phase alkylation reaction of ethylene and benzene.
[0053] The present disclosure is further described below by way of examples, but the examples do not disclose the scope of the present invention.
[0054] In the embodiments and comparative examples, the crystallinity of the molecular sieve is tested as follows: The relative crystallinity (RC) of the UZM-8 molecular sieve refers to the ratio of the sum of the peak areas of the five peaks of the calcined sample in the range of 2θ 16 to 27° to the sum of the five peak areas corresponding to the UZM-8 molecular sieve standard sample (calcined sample) (the crystallinity value is defined as 100%). The specific surface area and pore volume are tested by using a Micromeritic ASAP2010 static nitrogen adsorption instrument. Test conditions: The sample is placed in a sample processing system and vacuumed to 1.33×10 -2 Pa, constant temperature and pressure are maintained for 15 hours to purify the sample surface. At liquid nitrogen temperature -196 ° C, the adsorption and desorption of nitrogen by the purified sample under different pressure ratios P / P0 are measured to obtain adsorption-desorption isotherms. Then the two-parameter BET formula is used to calculate the specific surface area, and the adsorption amount below the pressure ratio P / P0≈0.98 is taken as the pore volume of the sample.
[0055] Example 1
[0056] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TMAOH: 0.1TEAOH: 0.3DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor, and hydrothermal crystallization reaction was carried out at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h, and a molecular sieve sample was obtained, numbered A1, and its XRD test results are as follows: Figure 1 As shown, the product is UZM-8 molecular sieve; SEM photos are shown Figure 2 As shown, it can be seen that the molecular sieve has a flaky structure; the crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0057] Example 2
[0058] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TMAOH: 0.05TEAOH: 0.3DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered A2, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0059] Example 3
[0060] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TMAOH: 0.3DEDMAOH: 13H2O. The raw material mixture was then transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. The product was taken out after cooling, filtered, washed, dried at 100°C for 16h and calcined at 580°C for 5h to obtain a molecular sieve sample, numbered A3, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0061] Example 4
[0062] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The colloidal molar ratio of the obtained raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TEAOH: 0.3DEDMAOH: 13H2O. Then the obtained raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 80°C for 24h and calcined at 600°C for 3h to obtain a molecular sieve sample, numbered A4, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0063] Example 5
[0064] Silica alumina colloid (SiO2 / Al2O3=25, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The colloidal molar ratio of the obtained raw material mixture colloid was SiO2: 0.04Al2O3: 0.1TMAOH: 0.1TEAOH: 0.3DEDMAOH: 13H2O. Then the obtained raw material mixture was transferred to a closed crystallization reactor, and hydrothermal crystallization reaction was carried out at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h, and a molecular sieve sample was obtained, numbered A5, and its XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0065] Example 6
[0066] Silica-alumina colloid (SiO2 / Al2O3=40, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.025Al2O3: 0.15TMAOH: 0.15TEAOH: 0.3DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 110°C for 15h and calcined at 540°C for 6h to obtain a molecular sieve sample, numbered A6, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0067] Example 7
[0068] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.05TMAOH: 0.05TEAOH: 0.5DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered A7, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0069] Example 8
[0070] Silica-alumina colloid (SiO2 / Al2O3=45, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.022Al2O3: 0.1TMAOH: 0.1TEAOH: 0.5DEDMAOH: 45H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 17 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 15h and calcined at 550°C for 6h to obtain a molecular sieve sample, numbered A8, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0071] Example 9
[0072] Silica alumina (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K), and alkaline source sodium hydroxide (analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the obtained raw material mixture colloid was 0.10NaOH:SiO2:0.05Al2O3:0.05TMAOH:0.05TEAOH:0.30DEDMAOH:13H2O. The obtained raw material mixture was then transferred to a closed crystallization kettle and subjected to hydrothermal crystallization reaction at 150°C for 10 days. The product was taken out after cooling, filtered and washed to obtain a solid filter cake, which was then exchanged twice with 2 mol / L ammonium nitrate solution at 75°C to make the alkali metal content in terms of alkali metal oxide less than 0.02% by weight. After drying at 120°C for 15h and calcining at 550°C for 6h, a molecular sieve sample was obtained, numbered A9, and its XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0073] Example 10
[0074] Silica alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetrapropylammonium hydroxide (TPAOH, 25% by weight, J&K), tetrabutylammonium hydroxide (TBAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TPAOH: 0.1TBAOH: 0.3DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 110°C for 12h and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered A10, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0075] Embodiment 11
[0076] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K), dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.1TMAOH: 0.1TEAOH: 0.3DEDMAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 165°C for 6 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered A11, whose XRD test results were consistent with Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0077] Comparative Example 1
[0078] UZM-8 molecular sieve was prepared according to the method of Example 2 of CN107661775B, specifically: silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free) and dimethyldiethylammonium hydroxide (DEDMAOH, 20% by weight, Bailingwei) were dissolved in deionized water, stirred and mixed evenly, and the colloid molar ratio of the obtained mixture was SiO2: 0.05Al2O3: 0.50DEDMAOH: 13H2O. Then the obtained mixture was transferred to a closed crystallization kettle, and hydrothermal crystallization reaction was carried out at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered D1, whose XRD test results were consistent with those of Figure 1 Similarly, it is shown that the product is UZM-8 molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve are measured and listed in Table 1.
[0079] Comparative Example 2
[0080] Silica-alumina colloid (SiO2 / Al2O3=20, Qingdao Ocean Chemical Plant, sodium-free), tetramethylammonium hydroxide (TMAOH, 25% by weight, J&K), and tetraethylammonium hydroxide (TEAOH, 25% by weight, J&K) were dissolved in deionized water and stirred to mix evenly. The molar ratio of the raw material mixture colloid was SiO2: 0.05Al2O3: 0.25TMAOH: 0.25TEAOH: 13H2O. Then the raw material mixture was transferred to a closed crystallization reactor and subjected to hydrothermal crystallization reaction at 150°C for 14 days. After cooling, the product was taken out, filtered, washed, dried at 120°C for 12h, and calcined at 550°C for 5h to obtain a molecular sieve sample, numbered D2. Its XRD test results showed that the product was Beta molecular sieve. The crystallinity, specific surface area and pore volume of the molecular sieve were measured and listed in Table 1.
[0081] Table 1
[0082] Example No. Molecular sieve number Crystallinity, % <![CDATA[Specific surface area, m 2 / g]]> <![CDATA[Pore volume, cm 3 / g]]> Example 1 A1 94.2 435 0.67 Example 2 A2 94.9 440 0.70 Example 3 A3 93.8 429 0.69 Example 4 A4 92.9 428 0.67 Example 5 A5 95.4 453 0.68 Example 6 A6 92.7 428 0.67 Example 7 A7 92.3 430 0.68 Example 8 A8 92.1 419 0.65 Example 9 A9 92.5 426 0.66 Example 10 A10 93.9 431 0.69 Embodiment 11 A11 92.7 422 0.67 Comparative Example 1 D1 90.5 410 0.63 Comparative Example 2 D2 90.8 560 0.62
[0083] It can be seen from the results in Table 1 that the UZM-8 molecular sieve disclosed in the present invention has high crystallinity, high specific surface area and pore volume. In addition, since lower-cost templates (such as TMAOH, TEAOH, TPAOH and TBAOH) are used to replace part of the more expensive template (DEDMAOH), the cost of the UZM-8 molecular sieve is reduced.
[0084] Test Example
[0085] The molecular sieves obtained in the examples and comparative examples were used to prepare catalysts and evaluate their alkylation performance.
[0086] The method for preparing the catalyst from the molecular sieve of Examples 1 to 11 and Comparative Examples 1 to 2 is as follows: molecular sieve (80% by weight on dry basis) and carrier dry rubber powder (70% by weight on dry basis, purchased from Sinopec Catalyst Changling Branch) are mixed evenly, and then nitric acid and an appropriate amount of deionized water are mixed into a uniform liquid and slowly added, mixing evenly while adding. The mass ratio of the obtained mixture is: 70% molecular sieve dry basis: 30% dry rubber powder dry basis: 100% deionized water (catalyst dry basis = molecular sieve dry basis + carrier dry basis, defined as 100%). The mixture is then further mixed evenly on an extruder, and then extruded into strips, dried, and roasted to obtain a catalyst.
[0087] The prepared catalyst was used for the alkylation reaction of benzene and ethylene. The reaction conditions were: benzene weight space velocity 3.0h -1 , benzene to ethylene molar ratio of 12, temperature 220°C, pressure 3MPa. Ethylene conversion and ethylbenzene selectivity were calculated according to the following formula, and the results are listed in Table 2.
[0088] Ethylene conversion (%) = (ethylene feed molar amount - unreacted ethylene molar amount) / ethylene feed molar amount × 100%
[0089] Ethylbenzene selectivity (%) = mass fraction of ethylbenzene / (100% - mass fraction of benzene - mass fraction of ethylene) × 100%
[0090] Table 2
[0091]
[0092]
[0093] It can be seen from the results in Table 2 that the catalyst disclosed in the present invention has a higher ethylene conversion rate and / or target product ethylbenzene selectivity in the process of synthesizing ethylbenzene by liquid phase alkylation reaction of ethylene and benzene.
[0094] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0095] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0096] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing UZM-8 molecular sieve, characterized in that: The method includes: Carrying out a hydrothermal crystallization reaction on a raw material mixture containing a silicon aluminum source, a first template, a second template and water, and recovering a product; Wherein, the first template agent is at least one selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, and the second template agent is dimethyldiethylammonium hydroxide.
2. The method according to claim 1, wherein: The molar ratio of the first template to the second template is (0.1-1):1, preferably (0.25-0.67):
1.
3. The method according to claim 1, wherein: The first template agent is tetramethylammonium hydroxide and tetraethylammonium hydroxide, and the molar ratio of the tetramethylammonium hydroxide to the tetraethylammonium hydroxide is (0.2-2):
1.
4. The method according to claim 1, wherein: The molar ratio of the raw material mixture includes: SiO2 / Al2O3=10-100, H2O / SiO2=8-50, R / SiO2=0.05-1.5; Preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15-40, H2O / SiO2=9-40, R / SiO2=0.1-0.9; More preferably, the molar ratio of the raw material mixture includes: SiO2 / Al2O3=15-30, H2O / SiO2=10-20, R / SiO2=0.3-0.5; Wherein, R represents the total molar number of the first template and the second template.
5. The method according to claim 1, wherein: The raw material mixture also contains an alkali source, and the molar ratio of the raw material mixture includes: B / SiO2=0.05-0.5, wherein B represents the molar number of the alkali source.
6. The method according to claim 5, wherein: The alkali source is at least one selected from sodium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide and cesium hydroxide.
7. The method according to claim 1, wherein: The silicon-aluminum source is silicon-aluminum gel.
8. The method according to claim 1, wherein: The conditions of the hydrothermal crystallization reaction include: a temperature of 130 to 180° C. and a time of 5 to 21 days; Preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 130 to 160° C. and a time of 7 to 17 days; More preferably, the conditions of the hydrothermal crystallization reaction include: a temperature of 150 to 160° C. and a time of 10 to 17 days.
9. UZM-8 molecular sieve prepared by the method according to any one of claims 1 to 8.
10. A catalyst, characterized in that The catalyst contains a carrier and the UZM-8 molecular sieve according to claim 9, and the content of the UZM-8 molecular sieve is 30 to 90% by weight, preferably 70 to 80% by weight, based on the dry weight of the catalyst.
11. Use of the catalyst according to claim 10 in liquid phase alkylation of ethylene and benzene, characterized in that: The application comprises: reacting ethylene and benzene in the presence of the catalyst at a reaction temperature of 180 to 260° C., a reaction pressure of 2.0 to 4.0 MPa, and a benzene weight space velocity of 1 to 5 h -1 , the alkylation reaction is carried out under the condition that the molar ratio of benzene to ethylene is (2-12):1.
Citation Information
Patent Citations
A catalyst containing UZM-8 molecular sieve and its application
CN107661775B
MWW-structure molecular sieve and preparation method thereof
CN105984879A
Catalyst containing UZM-8 molecular sieve and application of catalyst
CN107661775A
UZM-8 molecular sieve and synthesis method thereof
CN107662926A
Catalyst for selective opening of cyclic naphtha and process for using the catalyst
US20050101474A1